Examining the transnational health preferences of a group of Eastern European migrants relative to a European host population using the EQ-5D-5L. (February 2020) - Kelleher, Dan; Barry, Luke; Hobbins, Anna; O'Neill, Stephen; Doherty, Edel; O'Neill, Ciaran
Abstract: The concept of transnationalism may provide an alternative rationale to observed differences in patterns of migrant healthcare use and health-related behaviours. In this study, we examined the health preferences of Eastern European migrants residing in another European state relative to comparable natives through the prism of transnationalism. For the analysis, we focused on the health preferences of 87 Polish migrants living full-time in Ireland compared to 87 Irish natives. We used EQ-5D-5L composite Time Trade-Off (cTTO) utility data collected as part of the Irish value set during 2015/2016 to examine the health preferences of both groups. Propensity score matching was utilised to match comparable Irish respondents to Polish migrants with 1:1 matching. Since cTTO utility data is censored, a random effects Tobit model was used to explore differences in utility valuations, and in a secondary analysis, we examined the likelihood of applying a negative utility valuation using a random effects logit model. The results from this study demonstrate that on average Polish migrants apply a significantly greater disutility valuation to health states and are more likely to apply a negative utility valuation to a given health state when compared to comparable natives. Differences in utility valuations can be seen as indicative of time preference with a greater disutility valuation being associated with a higher rate of time preference. This finding may be suggestive of health-related behaviours, such as a greater likelihood of not engaging with preventive service use in as far as those with high rates of time preference have low uptake. Transnationalism can underpin the observed differences in health preferences between the Polish migrants and comparable Irish natives. Transnational ties shape health-related behaviours of migrants from the use of healthcare services to health preferences. The results of this study will be of interest to policymakers in Ireland and Europe. Highlights: Transnational ties shape health-related behaviours and health outcomes of migrants. Migrants have differing transnational health preferences compared to natives. Migrants apply a greater disutility value of 0.14 to a health state vs. natives. Migrants are more likely to value health states below zero (negatively) vs. natives.